Development of an energy-saving anaerobic hybrid membrane bioreactors for 2-chlorophenol-contained wastewater treatment. (December 2015) - Wang, Yun-Kun; Pan, Xin-Rong; Sheng, Guo-Ping; Li, Wen-Wei; Shi, Bing-Jing; Yu, Han-Qing
Abstract: A novel energy-saving anaerobic hybrid membrane bioreactor (AnHMBR) with mesh filter, which takes advantage of anaerobic membrane bioreactor and fixed-bed biofilm reactor, is developed for low-strength 2-chlorophenol (2-CP)-contained wastewater treatment. In this system, the anaerobic membrane bioreactor is stuffed with granular activated carbon to construct an anaerobic hybrid fixed-bed biofilm membrane bioreactor. The effluent turbidity from the AnHMBR system was low during most of the operation period, and the chemical oxygen demand and 2-CP removal efficiencies averaged 82.3% and 92.6%, respectively. Furthermore, a low membrane fouling rate was achieved during the operation. During the AnHMBR operation, the only energy consumption was for feed pump. And a low energy demand of 0.0045–0.0063 kWh m −3 was estimated under the current operation conditions. All these results demonstrated that this novel AnHMBR is a sustainable technology for treating 2-CP-contained wastewater.